Singing for dummies - Phillips, Pamelia S. (Pamelia Sue) (--For dummies., 2011)
This practical guide gives singers step-by-step instructions and lots of helpful tips, hints, vocal exercises, and reminders. The updated CD features new tracks and musical exercises, as well as demonstrations of popular technique, scales and pitch drills, and practice songs.